Automatic Wireless Mobile Weather Station - Vincent Vincent; Enndi Chiu; Kim Sung Tae; Ikhsan Bukhori; Surawan Setiyadi (Journal of Electrical And Electronics Engineering, 2020)
In the electronic devices, there are so many functions that we can use to make life easier. In the city especially, nearly all of them use technology as the system, it can also be used to store data, measuring data to help the others quantitative and qualitatively. One of the things that is very useful is the weather station, where the weather station used in the city to maintain the humidity, the intensity of the light, and the temperature. But in the rural areas, somehow the weather station is not available because of the limitation of the technology itself. And also, sometimes the place that we want to measure with is quite dangerous because there are so many predators. Because of that, we’ve come up to the new brand technology called Automatic Wireless Mobile Weather Station. This device helps us to measure the rural areas, dangerous places, using robot with wireless connection with weather station features. This device can be implemented into a moving robot and can also send us the data to the mobile phones through Bluetooth technology, and also it can measure the humidity, temperature, and the intensity of the light (unit of lux). Finally, the data can be controlled 24 hours through wireless connection, so we don’t really need to go into the location because we can control it using this Automatic Wireless Mobile Weather Station.